A blueprint for reform of the WTO agreement on agriculture - Valentin Zahrnt (European Centre for International Political Economy (ECIPE), 2009)
As the Doha negotiations are at a dead end, this paper takes a step back to address the future direction of WTO disciplines in agriculture. It puts members' negotiating positions and the draft modalities with their ever growing list of exceptions aside to focus on three fundamental questions. First, which agricultural policy instruments should be permitted or prohibited by WTO disciplines so as to best account for the manifold effects of agriculture on societies' welfare? Second, how should inefficient agricultural policies be treated as long as their removal is politically infeasible? And third, how can the WTO facilitate agricultural policy reform beyond establishing maximum thresholds for distorting policies? The paper argues for moving from the current "boxes" of domestic subsidies to a classification system that is more responsive to the differing degree of legitimacy of agricultural policy instruments. It also proposes to introduce "good governance" norms that guide members' decision-making in agriculture towards policies that are at the same time domestically efficient and internationally responsible.
Keywords: 330; WTO-Recht; Agrarpolitik; Agrarreform; Agrarsubvention; Agraraußenhandel; Good Governance; Welt